Some Remarks on Social and Symbolic Significance of the Early Neolithic Longhouses Based on the Applications and Spatial Distribution of Ground Stone Type Tools. The Case of the Linear Pottery Sites from Lesser Poland - Szydłowski, Marcin (Analecta Archaeologica Ressoviensia, 2022)
This article attempts to present some aspects of the spatial reconstruction, modes of use, and social relations in the longhouse settlements of the Linear Pottery culture (LBK) by means of a contextual distributional analysis of ground stone artefacts. Three LBK settlement complexes from Lesser Poland (southern Poland) were selected for analysis based on a considerable number of finds of ground stone tools yielded by the excavations. Accurate determination of the intended use of a stone object, as indicated by the traces of use on its surface, was of central importance. Based on the above data, the author has distinguished two types of household sectors in LBK settlements with longhouses, namely domestic and communal. It is argued that the inhabitants of a given longhouse used the domestic sector for their purposes, while the latter served the community. Significant differences in the proportions of ground stones were found between settlements and between the settlement phases of a village. This leads the author to consider whether there might have been specialized settlements for a particular microregion in addition to the function served by a single longhouse. Each settlement would have specialized in different household tasks.